2017
DOI: 10.3390/ijms18071419
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Wound Angiogenesis

Abstract: Diabetes Mellitus Type II (DM2) is a growing international health concern with no end in sight. Complications of DM2 involve a myriad of comorbidities including the serious complications of poor wound healing, chronic ulceration, and resultant limb amputation. In skin wound healing, which has definite, orderly phases, diabetes leads to improper function at all stages. While the etiology of chronic, non-healing diabetic wounds is multi-faceted, the progression to a non-healing phenotype is closely linked to poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
494
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 690 publications
(546 citation statements)
references
References 113 publications
6
494
1
4
Order By: Relevance
“…This is in accordance with several studies highlighting the importance of vessel maturation and timely return of VEGF to basal levels , warranting a fine balance between the expression of pro‐ and anti‐angiogenic factors within the healing wound. Moreover, TSP‐1, an anti‐angiogenic factor with an important role in vessel regression and ‘capillary pruning’ , was downregulated in the CAP‐treated wounds. PDGF plays a vital role in the resolution and maturation phase of wound angiogenesis and is currently the only FDA‐approved growth factor used for wound therapy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with several studies highlighting the importance of vessel maturation and timely return of VEGF to basal levels , warranting a fine balance between the expression of pro‐ and anti‐angiogenic factors within the healing wound. Moreover, TSP‐1, an anti‐angiogenic factor with an important role in vessel regression and ‘capillary pruning’ , was downregulated in the CAP‐treated wounds. PDGF plays a vital role in the resolution and maturation phase of wound angiogenesis and is currently the only FDA‐approved growth factor used for wound therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TSP‐1, an anti‐angiogenic factor with an important role in vessel regression and ‘capillary pruning’ , was downregulated in the CAP‐treated wounds. PDGF plays a vital role in the resolution and maturation phase of wound angiogenesis and is currently the only FDA‐approved growth factor used for wound therapy . Interestingly, our results showed that CAP treatment resulted in increased PDGFRβ levels in the mouse wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) affects nearly 10% of the U.S. population, and healthcare costs for diabetic patients are approximately 2.3 times greater than those for nondiabetic patients (CDC, ; Martin et al, ). Affected individuals often develop vascular changes that increase their risk for cutaneous wounds and infections (CDC, ; Okonkwo & Di Pietro, ). These problems are commonly managed with free flap reconstruction, but inherent impairments in wound healing and angiogenesis place diabetic patients at a higher risk of complications following surgical procedures (Okonkwo & Di Pietro, ).…”
Section: Introductionmentioning
confidence: 99%
“…Affected individuals often develop vascular changes that increase their risk for cutaneous wounds and infections (CDC, ; Okonkwo & Di Pietro, ). These problems are commonly managed with free flap reconstruction, but inherent impairments in wound healing and angiogenesis place diabetic patients at a higher risk of complications following surgical procedures (Okonkwo & Di Pietro, ).…”
Section: Introductionmentioning
confidence: 99%
“…Foot ulcers can affect people with both type 1 and type 2 diabetes Okonkwo and DiPietro, 2017 . People with diabetes ( ) may have reduced nerve functioning due to peripheral diabetic neuropathy.…”
Section: Introductionmentioning
confidence: 99%